PEER COUNSELING MODEL FOR IMPROVING STUDENTS’ SELF-DIRECTION COMPETENCE - Erhamwilda, Erhamwilda (UPI Press, 2014)
The purpose of this study is to test the effectiveness of the peer counseling model for improvingstudents’ self-direction competence. The research aimed to describe, test and analyze theeffectiveness of the peer counseling model and employed the descriptive-analytical methodand quasi-experiments to do this. The research activities consisted of a series of model validitytests, namely the model rationality test, the model practicability test, and the limited test. Thedata collection techniques were interviews, self-direction competence inventories, observationand documentation. The results of the research demonstrate that the peer counseling model asan intervention program for the experimental group as a whole proved to effectively improvestudents’ self-direction competence. The peer counseling model has its strengths in selfconfidence,self-reliance, and self-control.Keywords: effectiveness, peer-counseling model, students’s self-direction.